Effects of nano carbon on soil erosion and nutrient loss in a semi-arid loess region of Northwestern China - Zhou, Beibei; Chen, Xiaopeng; Wang, Quanjiu; Wei, Wei; Zhang, Tiancheng (International Journal of Agricultural and Biological Engineering, 2018)
Since 2005, the application of nano carbon (NC) in agriculture and environmental remediation has received considerable attention with most of the research focusing on plant growth and heavy metal absorption. However, little is known about the potential effects of NC on soil erosion and nutrient loss. In this study, rainfall simulation tests were conducted on a soil plot (1 m × 1 m, located in a semi-arid loess region of northwestern China), in which a mixture (5-cm below the soil surface) of NC (0, 0.1%, 0.5%, 0.7% and 1.0% on a mass base) and sandy soil (same as the one in the plot) was embedded as three bands (5 cm wide, 1 m long and 5 cm thick) at the three positions (top, middle and bottom of the plot), respectively. Before the rainfall simulation test, a mixed solution of potassium bromide (1.0 mol/L KBr), potassium nitrate (1.0 mol/L KNO3), monopotassium phosphate (1.0 mol/L KH2PQ4) was sprayed on the soil surface. Results showed that the sandy soil on the Loess Plateau with 0.7% NC addition (36.47 kg/hm2 on a mass basis) could improve soil water runoff, sediment yield, and nutrient loss in the semi-arid loess region of northwestern China, in addition to preventing soil water from deep percolation. Therefore, NC may have a great potential in soil erosion control on the Loess Plateau of China. Keywords: nano carbon, soil erosion, rainfall simulation tests, runoff, sediment, nutrient loss, semi-arid loess region DOI: 10.25165/j.ijabe.20181101.2775 Citation: Zhou B B, Chen X P, Wang Q J, Wei W, Zhang T C. Effects of nano carbon on soil erosion and nutrient loss in a semi-arid loess region of Northwestern China. Int J Agric & Biol Eng, 2018; 11(1): 138–145.